Scoping Study on Existing CIS and CSA Relevant Units and Engagements in Selected RUFORUM-member Zimbabwean Universities - Poshiwa, Xavier; Murungweni, Chrispen; Mudzengi, Clarice; Gwatibaya, Showman; Kupika, Olga; Sebele, Lovelater; Maphosa, Mcebisi (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
RUFORUM conducted a scoping study to identify areas of CSA and CIS convergence for selected Zimbabwean member universities from 20th November to March 2022. Consultations were made with the Deans of the Faculties of Agriculture and related disciplines of member universities through zoom and then individual questionnaires to identify the focal persons who are involved in Climate Smart Agriculture teaching and research. Two staff members from Zimbabwe representing Africa-wide countries participated in a three-day workshop in Benin as a side event during the RUFORUM Triennial Conference and Annual General Meeting (https://www.ruforum.org/Triennial2021/ https://www.ruforum.org/AGM2022) from 11th to 13 December 2021. The two members participated in a meeting together with CSA and CIS experts representing 9 countries: Kenya, Zambia, Ethiopia, the Democratic Republic of Congo, Benin, Burundi, Uganda, Ghana and Zimbabwe. The experts analyzed the causes of low adoption and utilization of CSA practices & CIS tools and identified the different interventions needed to enhance this shortcoming. Seven priorities were identified, and it was agreed that the proposed priority CSA be subjected to national wide consultations in the respective countries. This report was compiled to meet the following objectives: i) review and compile information about CSA and conduct an inventory of existing programmes and courses related to CSA and potential resource persons in Zimbabwean universities, and ii) conduct country-specific consultations and consensus building on the priority CSA. The report showed that in the 4 Universities sampled, various courses and course units with aspects of CSA and CIS are taught. These courses cover a wide range of the proposed clustered priority areas and are course units offered for undergraduate programmes. Furthermore, the national consultations revealed that the Zimbabwean government has a high level of commitment to CSA/CIS mainstreaming adaptation and mitigation goals into agricultural planning processes and has developed several climate policy & legislative frameworks. These policies were identified and prioritized for CSA intervention.